2018
DOI: 10.4314/mmj.v30i1.1
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence and frequency of genomic mutations that mediate Isoniazid and Rifampicin resistance in Mycobacterium tuberculosis isolates from untreated pulmonary Tuberculosis cases in urban Blantyre, Malawi

Abstract: BackgroundThe emergence and spread of drug-resistant Tuberculosis (TB) is a major public health threat. TB resistance originates in the course of treatment due to genomic mutations in Mycobacterium tuberculosis (MTB). An increase in new cases with drug-resistant TB could be an indicator of high levels of circulating resistant strains. This study was conducted to determine the occurrence and frequency of genomic mutations that mediate Isoniazid (INH) and Rifampicin (RIF) resistance among isolates from untreated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“… 12 , 27 Moreover, the study reported from Malawi indicated that the S315T1 mutation and the mutation in the inhA gene that occurred in C15T are associated with INH resistance. 37 However, a study in India showed a higher proportion of C15T mutations. 27 Similarly, a study reported from Sudan found a C15T mutation that resulted in INH resistance.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“… 12 , 27 Moreover, the study reported from Malawi indicated that the S315T1 mutation and the mutation in the inhA gene that occurred in C15T are associated with INH resistance. 37 However, a study in India showed a higher proportion of C15T mutations. 27 Similarly, a study reported from Sudan found a C15T mutation that resulted in INH resistance.…”
Section: Discussionmentioning
confidence: 98%
“… 27 , 35 , 36 However, our finding was similar to the previous study reported from Ethiopia and Sudan in S531L and H526Y mutations. 37 , 38 …”
Section: Discussionmentioning
confidence: 99%
“…The first step in easing the burden of DR-TB is to comprehend the geographical distribution of the disease and identify regions with the greatest prevalence of notified cases [29]. Drug resistance in Mtb is singularly mediated by chromosomal mutations [31]. Our study detected mutations in rpoB, katG and inhA from the four municipalities.…”
Section: Discussionmentioning
confidence: 93%
“…Strategic measures in combating the spread of DR-TB include active surveillance, screening for DR-TB, early isolation, and management of confirmed cases [31]. The first step in easing the burden of DR-TB is to comprehend the geographical distribution of the disease and identify regions with the greatest prevalence of notified cases [29].…”
Section: Discussionmentioning
confidence: 99%
“…The most highly resistant forms of TB have been described in the literature in a number of different ways, aside from XDR-TB. These include: total drug-resistant TB, 27 , 28 totally drug-resistant TB, 11–14 (TDR-TB), super extensively drug-resistant TB (SXDR-TB or super XDR-TB), 12 , 29 extra extensively drug-resistant TB (XXDR-TB), 11 , 30 pan-resistant TB, 36 , 37 pan drug-resistant TB (PDR-TB), 30 – 33 , 38 , 39 untreatable TB, 34 , 35 , 40 untreatable drug-resistant TB, 36 , 37 incurable TB, 20 , 41 and incurable drug-resistant TB. 42 , 43 The term extremely drug-resistant TB has also, in some cases, been given the same abbreviation as extra extensively drug-resistant TB (XXDR-TB), 38 , 42 and, in others, the same as abbreviation as extensively drug-resistant TB (XDR-TB) 39 , 40 In order to account for this variation in terminology, all of these terms were included as search terms in our review.…”
Section: Methodsmentioning
confidence: 99%